2016
DOI: 10.1371/journal.pone.0160080
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Hybridization in Pilot Whales and Asymmetric Genetic Introgression in Northern Globicephala melas under the Scenario of Global Warming

Abstract: Pilot whales are two cetacean species (Globicephala melas and G. macrorhynchus) whose distributions are correlated with water temperature and partially overlap in some areas like the North Atlantic Ocean. In the context of global warming, distribution range shifts are expected to occur in species affected by temperature. Consequently, a northward displacement of the tropical pilot whale G. macrorynchus is expected, eventually leading to increased secondary contact areas and opportunities for interspecific hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…Such a spatial component is consistent with some degree of population structuring, which combined with the connectivity network (between some of the areas/archipelagos and an outside area) suggest that short‐finned pilot whales have developed a complex social and geographical ecology. Although the social analysis has showed that none of the clusters composed by the individuals captured in Madeira and the Azores were linked to the clusters composed by the individuals captured in Madeira and the Canaries, the absence of genetic population differentiation in this species in the study area (Alves, Quérouil, et al., ; Miralles et al., ) suggests that it may be an artefact of an insufficient sample size and that it supports the findings described here. Ecological spatial structuring has been also suggested for other delphinid populations occupying large areas, that is, over hundreds or thousands of kilometres.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Such a spatial component is consistent with some degree of population structuring, which combined with the connectivity network (between some of the areas/archipelagos and an outside area) suggest that short‐finned pilot whales have developed a complex social and geographical ecology. Although the social analysis has showed that none of the clusters composed by the individuals captured in Madeira and the Azores were linked to the clusters composed by the individuals captured in Madeira and the Canaries, the absence of genetic population differentiation in this species in the study area (Alves, Quérouil, et al., ; Miralles et al., ) suggests that it may be an artefact of an insufficient sample size and that it supports the findings described here. Ecological spatial structuring has been also suggested for other delphinid populations occupying large areas, that is, over hundreds or thousands of kilometres.…”
Section: Discussionsupporting
confidence: 75%
“…To estimate residency times, we applied the initial models developed by Whitehead (). These models provided an opportunity to analyse movements into and out of each archipelago, which is known to occupy only a portion of the animals’ range (Alves, Quérouil, et al., ; Miralles, Oremus, Silva, Planes, & Garcia‐Vazquez, ).…”
Section: Methodsmentioning
confidence: 99%
“…After adding previously published sequences from other oceanic basins 20,[23][24][25][26] , a total of 15 haplotypes were obtained after the elimination of the site that was generating phylogeographic noise in the total 1012 sequences. This led to the combination of four previously described haplotypes in the following pairs: S with R, P with U, Q with Y, and E with G ( Table 1).…”
Section: Global Diversity Analysismentioning
confidence: 99%
“…A colonization event from south to north would have taken place through a founder effect, followed by demographic population growth. Additional genetic research on pilot whales has been conducted mostly at the population level in the North Atlantic and Mediterranean Sea [23][24][25] , however, an integration of this available information is missing, together with the sampling of other areas such as the southeastern Pacific.…”
mentioning
confidence: 99%
“…importance of cruising vs. maneuverability for different foraging behaviours) in assessing differences in the size of their appendages (Berta, Sumich, & Kovacs, ; Domenici, ; Woodward, Winn, & Fish, ). However, short‐finned pilot whales and long‐finned pilot whales are closely related species that diverged only about 648,500 years ago (Miralles, Oremus, Silva, Planes, & Garcia‐Vasquez, ) and are generally similar morphologically, but show contrasting distributions in the North Atlantic Ocean (Hayes, Josephson, Maze‐Foley, & Rosel, ; Figure ). Short‐finned pilot whales occur in tropical and subtropical waters, while long‐finned pilot whales show a more temperate distribution (Leatherwood, Caldwell, & Winn, ).…”
Section: Introductionmentioning
confidence: 99%